Penerapan Prinsip POACE (Planning, Organizing, Actuating, Controling, Evaluation) dalam Pemberdayaan Masyarakat - Susanto, Agus (INTELEKSIA: Jurnal Pengembangan Ilmu Dakwah, 2022)
This study examines the implementation of POACE (Planning, Organizing, Actuating, Controlling, Evaluation) in community empowerment activities. This study uses the literature review method with secondary data sources, while the results of this research are: community workers and communities must be able to: (1) Set community empowerment goals collectively, which are able to provide optimistic encouragement to be achieved together. (2) Setting targets for community empowerment, so that goals do not become imaginary desires. (3) Analyzing the community environment, finding internal community assets and external assets that might be utilized. (4) Determine the community empowerment strategy. Meanwhile, in the organizing stage, community workers and the community must be able to: (1) Analyze community empowerment programs. (2) Grouping the jobs in the community empowerment program so that they do not overlap. (3) Make a container for work groups, or commonly called divisions/departments. (4) Analyzing HR capacity with the needs or requirements of a department, but the starting point is HR potential. (5) Placing HR into the departments that have been created. In mobilizing, community workers together with the community must be able to carry out: (1) Clear and simple directions. (2) Provision of Trouble Solving when experiencing problems. (3) Providing role models from the community itself in order to motivate other members. (4) Motivate. In the control stage, community workers and the community must be able to: (1) Monitor or supervise the performance of community human resources. (2) Input-based evaluation is not just criticism of mistakes. The implication of this study is that the efficiency and effectiveness of managing empowerment management activities in the community will be more guaranteed than if the implementation of empowerment ignores the paradigm of management functions.